MANAGEMENT OF DUSHTA VRANA BY JATYADI GHRITA - Sharma Rishu; Sharma Nisha; Prasad Anjali B; Agrawal Sachin (International Journal of Applied Ayurved Research, 2016)
Background and objectives: Ulcer is a discontinuity, often excavation of skin exhibiting loss of epidermis and portion of the dermis and even subcutaneous fat. Under normal physiological condition healing is inevitable. The process of healing is divided in to four phases’ viz. hemostasis, inflammation, proliferation and remodeling. Among various factors affecting process of healing oxygenation, infection, age and sex hormones, stress, diabetes, obesity, medications, alcoholism, smoking, and nutrition of which infection is our prime concern. Vrana stated in Ayurveda simulates Ulcers or wound; which may get converted in to Dushta Vrana i.e. infectious or complicated wound in due course of time. Precise management of Dushta Vrana has been described in various Ayurvedic texts. Many formulations are in use for centuries. One of these is a poly herbal drug Jatyadi Ghrita. The objective of the present study is to evaluate the effect of Jatyadi Ghrita on the basis of relief in signs and symptoms of Dushta Vrana. Methods: The effect of Jatyadi Ghrita was studied on 30 patients of Vrana on the basis of relief obtained on subjective and objective parameters and assessing the result applying paired t-test & percentage of relief on the signs and symptoms of Dushta Vrana. Duration of the Study was 45 days; initially daily dressing done for one week and next 38 days weekly dressing was done followed by regular 2 months follow up was done. Results: The results observed based on the relief obtained on the subjective and objective parameters taken for consideration for this study viz. Size of ulcer, Discharge, Foul Smell, Pain, Burning Sensation, Itching Sensation, Granulation and Sloughing and were found significant (P<0.05) on all the above parameters by applying paired t-test . Conclusion: It showed that Jatyadi Ghrita significantly helped in reduction of the signs and symptoms of the Dushta Vrana, enhancing wound healing process and reducing the morbidity of the patients.